Penggunaan Cangkang Kemiri Sebagai Subtitusi Agregat Kasar Dan Zat Tambah Terhadap Sifat Mekanis Beton - Haris, Zainal Abidin; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Indonesia is a developing country that is improving public infrastructure development, which serves to support the continuity of services to the community. Research that has often been carried out in general generally uses a simple technology by utilizing local resources including the use of waste as a building material, one of which is pecan shells. The purpose of this study was to obtain the effect of partial substitution of crushed stone with a kemeiri shell by 5% and the addition of various added substances by 0.6% of the weight of cement on the compressive and tensile strength of concrete. There were 47 samples made, including 23 samples of normal concrete and 24 samples of variation concrete. Concrete samples were soaked for 28 days before testing the compressive strength and tensile strength of concrete. The results of this test showed that pecan shell mixed concrete experienced a decrease in compressive and tensile strength values compared to normal concrete, while in pecan mixed concrete variations of various added substances experienced higher compressive and tensile strength values than pecan mixed concrete.